Hypomagnesemia In Alcohol Dependent Population From The Lower Socio-Economic Background Who Were Consuming Illicit Liquor And Attending The De-Addiction Center - SAMEER R KULKARNI; K.PRATIBHA RAVINDRA; CHITRA Y.DHUME; EDMOND RODRIGUES; MILIND KARAPURKAR (International Journal of Pharma and Bio Sciences, 2012)
Magnesium is intimately involved in over 300 enzymatic reactions, particularly in processes involving the formation and utilization of ATP. It is also a known fact that alcoholism is associated with hypomagnesaemia.The present study determines the significance of routine serum magnesium determination in alcoholic patients consuming illicit liquor from lower socio-economic background attending deaddiction centre. Serum magnesium, sodium and potassium concentrations in 200 chronic alcoholic patients consuming illicit liquor from lower socio-economic background admitted to the deaddiction centre were estimated and compared to 158 healthy nonalcoholic controls.Serum magnesium levels were significantly decreased whereas serum transaminases and gammaglutamyl transpeptidases were increased in alcoholic patients compared to healthy nonalcoholic controls.Hypomagnesemia could be due to the increased oxidative stress and might be a risk factor in the progression of fatty liver to steatohepatitis.The results of the present investigation support the practice of routine magnesium administration to chronic alcoholics.